All‐in‐One: Photo‐Responsive Lanthanide‐Organic Framework for Simultaneous Sensing, Adsorption, and Photocatalytic Reduction of Uranium - Huang, Zhi‐Wei; Li, Xiao‐Bo; Mei, Lei; Han, Yi‐Zhi; Song, Yu‐Ting; Fu, Xuan; Zhang, Zhi‐Hui; Guo, Zhi‐Jun; Zeng, Jian‐Rong; Bian, Feng‐Gang; Wu, Wang‐Suo; Hu, Kong‐Qiu; et al. (Advanced functional materials, 2024)
The selective removal and immobilization of uranyl ions from aqueous solutions is essential for the sustainable development of nuclear energy. Herein, a robust lanthanide‐organic framework material (IHEP‐24) is developed for simultaneous fluorescence sensing, selective adsorption, and photocatalytic reduction of uranium, integrating three different functions in one material. The confined space formed by the coordination assembly of viologen derivative ligands and metal‐oxygen clusters can act as precise recognition sites for uranyl, allowing IHEP‐24 to efficiently detect and capture uranyl ions. In addition, the presence of a viologen‐based radical ligand enables IHEP‐24 to a further photocatalytic reduction of the adsorbed uranyl to amorphous UO2. The mechanisms of adsorption and photocatalysis are revealed by batch experiments, photoelectrochemical characterizations, and theoretical calculations. This study provides a reference for the construction of robust multi‐functional MOF materials and also provides support for the deep removal and immobilization of radionuclides from aqueous solution. A series of robust viologen‐based photo‐responsive metal–organic frameworks with isomorphic structures are reported, capable of achieving simultaneous fluorescence sensing, adsorption, and photocatalytic reduction of uranium. The presence of viologen‐based radical ligands enhances the efficiency of the photocatalytic reduction of adsorbed uranyl to amorphous UO2, facilitating the deep purification of uranyl in aqueous solution.